Pembelajaran non-formal di kalangan orang dewasa: kajian perbandingan antara petani,nelayan dan peneroka Felda - Md. Junoh, Adnan; Abdul Hamid, Mohd. Azhar (Faculty of Management and Human Resource Development, 2004)
Non-formal learning is an important mode of adult learning for theacquisition of the knowledge and skills. Therefore, the objective of thestudy is to identify the non-formal learning pattern amongst farmers,fishermen and Felda Settlers. One hundred farmer, fisherman and FeldaSettlers were selected as a respondent of the study. The data was collectedusing a set of questionnaire specifically design for the study. TheStatistical Package For Social Science (SPSS) was employed to analyzethe research data for descriptive statistic, Pearson correlation, Khi squaretest of homogeneity and ANOVA.The study indicates that majority of the respondent actively participate innon-formal learning and possess a positive attitude toward learning andself-esteem. The major leaning content is religion and politic relatedmatters. Mosque recorded as the main learning site for the non-formallearning. Meanwhile, lecture recorded as the major learning method. Thestudy also indicates that the primary motive of participation in non-formallearning is gaining rewards from the God. Time constrain is the mainlearning problems. The study also revealed that there is no significancedifference of the non-formal learning pattern between farmers, fishermenand Felda Settlers.The study concludes that non-formal learning is important mode oflearning amongst farmers, fisherman and Felda Settler. Non-formallearning is part of their daily life activities influence by socio-culturalfactors.